Labor Market Outcomes of Vocational High Schools (SMK) and General High Schools (SMA) during the COVID-19 Pandemic - Nurul Fajri Vidi Astuti; Diahhadi Setyonaluri (The Journal of Indonesia Sustainable Development Planning, 2022)
The fourth Sustainable Development Goals (SDGs) adopts a lifelong learning approach to education and introduces vocational and tertiary education into the global agenda. While Vocational Education and Training (VET) was almost absent in previous international development frameworks, the agenda 2030 and its SDGs highlight greater importance to it. Consequently, many governments in developing countries promote vocational secondary education to improve labor market outcomes. This study aimed to determine the development of return on investment for Vocational High Schools (SMK) and Senior High Schools (SMA) in 2020. The data used the August 2020 National Labor Force Survey (SAKERNAS) data with Two-Step Heckman and the Mincer Revenue Function. As a result, in 2020, the return on investment in vocational education was 16.82% higher than the rate of return on investment in high school education. However, observed by the age group, the results show that SMK only provides an initial wage advantage for men, which then declines with age. Although male SMK graduates experienced poorer results, female SMK graduates did not experience the same decline.